2009
DOI: 10.1177/026248930902800603
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on Microstructural, Surface Hardness and Flexural Strength of Injection Molded Microcellular Foamed Parts

Abstract: This paper presents an experimental study on microstructural and mechanical properties of injection molded microcellular foamed parts. The effects of shot size, injection pressure and mold temperature on the relative density, unfoamed skin thickness, cell population density, surface hardness and flexural strength of various regions of the injected parts were investigated. A conventional injection molding machine was modified to produce microcellular acrylonitrile butadiene styrene (ABS) foamed plates. Nitrogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 13 publications
2
16
0
Order By: Relevance
“…Nevertheless, foamed samples presented the opposite trend, with higher flexural modulus and strength at the end areas, as also reported by Rezavand et al 27 This tendency could be due to the thicker skin layers. When samples are taken in TD direction, no great differences are detected in the three tested sections, because of the more homogeneous morphology generated in the center of the plate.…”
Section: Flexural Propertiessupporting
confidence: 72%
“…Nevertheless, foamed samples presented the opposite trend, with higher flexural modulus and strength at the end areas, as also reported by Rezavand et al 27 This tendency could be due to the thicker skin layers. When samples are taken in TD direction, no great differences are detected in the three tested sections, because of the more homogeneous morphology generated in the center of the plate.…”
Section: Flexural Propertiessupporting
confidence: 72%
“…A slight reduction in the flexural modulus and strength of solid samples can be observed in TD direction, which might be due to a slight decrease in the packing pressure at the end of the cavity. Nevertheless, foamed samples presented the opposite trend, with higher flexural modulus and strength at the end areas, as also reported by Rezavand et al [226]. This tendency could be due to the thicker skin layers.…”
Section: Flexural Behaviorsupporting
confidence: 71%
“…These two cell forming processes would give a clear understanding of cell structure in former researchers' study. Yuan et al found that as the weight reduction increases, a high degree of cell shear deformation can be seen in the SEM micrographs along the melt flow direction, and this phenomena will be easily explained with the principle of cell forming process. As there are two cell forming processes in the microcellular injection molding, when the weight reduction increases, the cells formed in “foam during filling” process will not dissolve into the melt and retain in the part finally.…”
Section: Resultsmentioning
confidence: 99%
“…In the aspect of cell structure researches, Behravesh and Rajabpour carried out an experimental research on the filling stage of microcellular injection molding process and found that the shot size has a dominant effect on foam or cell structure, too low a shot size causes a nonuniform microstructure and incompletely foamed part, and at too high a shot size, the gas will remain dissolved in the polymer matrix. The similar results was found by Yuan et al, they studied the microcellular injection molding of polyamide‐6 nanocomposites, proposed that the shot size appears to be the most predominant molding parameter affecting the cell size and cell density; whereas, for the same part with the same shot size, Rezavand et al found that cell size, cell distribution, and skin thickness are different at various regions. For microcellular injection‐molded nanocomposites, Hwang et al recently found that the cell size decreased as the clay loading increased in microcellular thermoplastic olefin elastomers (TPO)–clay nanocomposites and ethylene vinyl acetate (EVA)–clay nanocomposites.…”
Section: Introductionmentioning
confidence: 99%